The Shared Values of Sharia Banking: Non-Muslims Under The Qanun on Islamic Financial Institutons in Aceh - Alidar, EMK; Maulana, Muhammad; Ramly, Arroyyan; Filzah, Nadhilah (AHKAM : Jurnal Ilmu Syariah, 2024)
The implementation of the Qanun No. 11/2018 on Sharia Financial Institutions (SFIs) has led all conventional banks to suspend their operation in Aceh. The Qanun has imposed Acehnese people to use sharia banking services. It raises the question of the extent non-Muslims accept the implementation of the Qanun on SFIs considering their civil rights and how they view the Qanun in terms of their religiosity, legal compliance, and motivation for submitting to it. This study aims to analyze the reasons why non-Muslims submit to and comply with the Qanun, as well as their experiences in receiving sharia banking services. This juridical and empirical legal research collected data from observation and in-depth interviews with nine respondents in several districts in Aceh and three people outside Aceh. It concludes that non-Muslims are generally in favor of the Qanun's implementation. They do not mind utilizing sharia financial products and services, and the Qanun's provisions do not restrict their access and interests. The administration of the banks can generally satisfy the legal requirements of offering sharia banking clients quality services irrespective of their religious background. All engagement elements are fulfilled under the civil law. The sharia banking principles has not only become shared values among different religious adherents in Aceh but also do not conflict with non-Muslim customers' beliefs, religions, and rights in terms of the priniciple of equality before the law. Abstrak: Penerapan Qanun Nomor 11 Tahun 2018 tentang Lembaga Keuangan Syariah (LKS) telah menyebabkan seluruh bank konvensional menghentikan operasionalnya di Aceh. Qanun tersebut telah mewajibkan masyarakat Aceh untuk menggunakan layanan perbankan Syariah. Hal ini menimbulkan pertanyaan sejauh mana non-Muslim menerima penerapan Qanun tentang LKS dengan mempertimbangkan hak-hak sipil mereka dan bagaimana mereka memandang Qanun dalam kaitannya dengan keberagamaan, kepatuhan hukum, dan motivasi untuk tunduk pada Qanun tersebut. Penelitian ini bertujuan untuk menganalisis alasan non-Muslim tunduk dan patuh terhadap Qanun, serta pengalaman mereka dalam menerima layanan perbankan syariah. Penelitian hukum yuridis dan empiris ini mengumpulkan data melalui observasi dan wawancara mendalam terhadap sembilan responden di beberapa kabupaten di Aceh dan tiga orang di luar Aceh. Laporan ini menyimpulkan bahwa non-Muslim pada umumnya mendukung penerapan Qanun tersebut. Mereka tidak keberatan memanfaatkan produk dan jasa keuangan syariah, serta akses dan kepentingan mereka tidak dibatasi oleh ketentuan Qanun. Secara umum, administrasi bank dapat memenuhi persyaratan hukum dalam menawarkan layanan berkualitas kepada klien perbankan syariah terlepas dari latar belakang agama mereka. Seluruh unsur perikatan dipenuhi berdasarkan perspektif hukum perdata. Prinsip perbankan syariah tidak hanya menjadi nilai bersama antar umat beragama di Aceh tetapi juga tidak bertentangan dengan keyakinan, agama, dan hak nasabah non-Muslim dalam prinsip kesetaraan di hadapan hukum.